2017
DOI: 10.1093/cercor/bhx016
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Inhibition within Layer IV of Sert Knockout Rat Barrel Cortex is Associated with Faster Sensory Integration

Abstract: Neural activity is essential for the maturation of sensory systems. In the rodent primary somatosensory cortex (S1), high extracellular serotonin (5-HT) levels during development impair neural transmission between the thalamus and cortical input layer IV (LIV). Rodent models of impaired 5-HT transporter (SERT) function show disruption in their topological organization of S1 and in the expression of activity-regulated genes essential for inhibitory cortical network formation. It remains unclear how such alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 102 publications
2
48
0
Order By: Relevance
“…The spontaneous tactile object localization (Celikel and Sakmann, 2007) experiments were performed on 11 male Wistar rats (Harlan Laboratories, The Netherlands). Animal handling, behavioral observations and behavioral experiment paradigm were as described before (Azarfar et al, 2018b) and were comparable to the previous studies utilizing the same task (Celikel and Sakmann, 2007;Voigts et al, 2008Voigts et al, , 2015Pang et al, 2011;Juczewski et al, 2016;Miceli et al, 2017). In short, on this task animals shuttle between two elevated platforms with a variable distance between them as a camera placed over the gap between the two platforms is used to visualize the body and whisker position ( Fig.1A).…”
Section: Methodsmentioning
confidence: 79%
See 2 more Smart Citations
“…The spontaneous tactile object localization (Celikel and Sakmann, 2007) experiments were performed on 11 male Wistar rats (Harlan Laboratories, The Netherlands). Animal handling, behavioral observations and behavioral experiment paradigm were as described before (Azarfar et al, 2018b) and were comparable to the previous studies utilizing the same task (Celikel and Sakmann, 2007;Voigts et al, 2008Voigts et al, , 2015Pang et al, 2011;Juczewski et al, 2016;Miceli et al, 2017). In short, on this task animals shuttle between two elevated platforms with a variable distance between them as a camera placed over the gap between the two platforms is used to visualize the body and whisker position ( Fig.1A).…”
Section: Methodsmentioning
confidence: 79%
“…14.5+ cm for adults and 9+ cm for juvenile, were used for further analysis. These distances were selected to ensure that only tactile exploration of whisker touch was quantified, as animals also use the touch receptors around their nose in shorter gapdistances (Celikel and Sakmann, 2007;Voigts et al, 2008Voigts et al, , 2015Pang et al, 2011;Juczewski et al, 2016;Miceli et al, 2017). Whisker protraction was quantified in respect to the midpoint of the whisk space which was defined by the most protracted and retracted positions, normalized to the nose position, during the tactile exploration epoch.…”
Section: Analysis Of Tactile Explorationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, if the experimental design requires targeted alteration of molecular/cellular function, upon, e.g., sensory deprivation (Celikel et al, 2004;Foeller, Celikel, & Feldman, 2005), induction of synaptic plasticity in identified pathways (Allen et al, 2003;Clem, Celikel, & Barth, 2008), systematic modulation of cellular excitability (Huang et al, 2016;Juczewski et al, 2016;Miceli et al, 2017), circuit alterations (Corsini et al, 2009;Freudenberg et al, 2013aFreudenberg et al, , 2013bFreudenberg et al, , 2016Seib et al, 2013), or behavioral training (Celikel & Sakmann, 2007;Seib et al, 2013;Voigts, Herman, & Celikel, 2015), it would be advisable to design the experiments to ensure availability of within-animal and within-slice (wherever applicable) controls to minimize the genomic variability across independent samples and the experimental groups.…”
Section: Of 21mentioning
confidence: 99%
“…RNA and protein collected in this way is of sufficient quality to be used in high‐throughput techniques (i.e., RNA sequencing and mass spectrometry), making ABSM highly useful for the elucidation of molecular mechanisms in the brain. The method is easily applicable in any cellular/molecular or (neuro)physiology lab, as it is an expansion of the acute electrophysiological slice preparation commonly used in the central nervous system (see, e.g., Allen, Celikel, & Feldman, ; Celikel et al., ; Celikel, Szostak, & Feldman, ; Huang, Resnik, Celikel, & Englitz, ; Miceli et al., ). Because the method uses living tissue, ABSM has several advantages over other tissue isolation techniques (see Commentary).…”
Section: Introductionmentioning
confidence: 99%